Association between serum uric acid and inflammation markers in ankylosing spondylitis patients treated with tumor necrosis factor-α or nonsteroidal anti-inflammatory drugs - Sargın, Betül; Gürer, Gülcan; Taşcı Bozbaş, Gülnur; Öztürk, Hakan (The European Research Journal, 2019)
Objectives: Uric acid has an important role in the production of various inflammatory cytokines such as tumor necrosis factor-α (TNF-α). Although serum uric acid levels in various rheumatic diseases have been performed the relationships between serum uric acid levels with inflammatory markers and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores in ankylosing spondylitis patients treated with anti-TNF-α and nonsteroid anti-inflammatory drugs (NSAIDs) have not been described yet. The aim of this study was to compare the relationships between serum uric acid levels, inflammatory markers and BASDAI scores in ankylosing spondylitis patients treated anti-TNF-α and NSAIDs. Methods: A total of 132 ankylosing spondylitis patients fulfilling the 1984 Modified New York Criteria who had serum uric acid, erythrocyte sedimentation rate and C-reactive protein levels in medical records were included in this retrospective cross-sectional study. Patients were divided in two groups (anti-TNF-α and NSAIDs). Their files were examined in detail. Later demographic and laboratory features were recorded to the research form. Results: Serum uric acid levels were significantly lower in the anti-TNF-α group (mean: 4.9 mg/dL, range: 4.10-5.45 mg/dL) than in the NSAIDs group (mean: 5.20 mg/dL, range 4.70-5.90 mg/dL) (p = 0.021). Also, positive correlations were found between C-reactive protein (p = 0.003) and BASDAI (p = 0.009) with serum uric acid. Conclusions: According to this study, we can consider that serum uric acid level could be used as an inflammatory laboratory marker, such as C-reactive protein in ankylosing spondylitis patients. However, we believe that more studies are needed about this research.